Efektivitas Pelayanan Administrasi Terpadu Kecamatan (Paten) Terhadap Pelayanan Publik di Kantor Camat Banyuasin III Kabupaten Banyuasin - Khoirudin Khoirudin; Ignasius Hendrasmo; Muhammad Abduh (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Khoirudin. Effectiveness of District Integrated Administration Services (PATEN) on Public Services at the Banyuasin III Sub-district Office of Banyuasin Regency. This study aims to describe the effectiveness of the District Integrated Administration Service (PATEN) on public services at the Banyuasin III District Head Office, Banyuasin Regency. This research was conducted for three months using a quantitative approach. Data was collected through questionnaires, observation, and documentation. Data analysis techniques are carried out by presenting data, reducing data, and drawing conclusions. The results showed that the organizational characteristics in Banyuasin III District in providing administrative services were quite good, where the organizational structure and management went well, each employee had individual skills and abilities that could be developed as well as good adaptability in dealing with situations. certain situations. Environmental characteristics, in administrative services in the District, can be said to be able to read the environmental situation and adjust to existing conditions, meaning that they continue to learn and work well in order to serve the needs of the community in today's modern era. Employees, besides that they must continue to learn and develop in the face of the increasing needs of the community in managing administration in the District, on the other hand they must also behave well and be trustworthy in carrying out their duties. Vertical and horizontal communication at the Banyuasin III District Office has been running well. Then for the reward itself, although it has not been fully implemented, it has been carried out gradually to improve employee performance. As for the attention to employees is quite good.